Preparation method and application of modified zinc-manganese spinel denitration catalyst based on zinc plating scum

By extracting zinc from galvanized scum and combining it with manganese ions and dopants to prepare a modified zinc-manganese spinel catalyst, the problems of insufficient catalytic activity and high cost are solved, and efficient medium and low temperature denitrification and galvanizing are achieved. The resource utilization of scum improves the performance and economics of the catalyst.

CN119140087APending Publication Date: 2024-12-17WUHAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411275021.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing medium and low temperature denitrification catalysts have insufficient catalytic activity and high cost, making it difficult to effectively reduce the treatment cost of galvanized scum, which limits its wide application.

Method used

Using galvanized scum as zinc source, zinc ions are extracted through zinc leaching liquid, combined with manganese ions and appropriate dopants, and modified zinc-manganese spinel denitrification catalyst is prepared through precipitation and calcination to improve catalytic performance and reduce the Preparation cost.

Benefits of technology

The performance of medium and low temperature denitrification catalysts has been significantly improved, and the NO removal rate reaches 92%, while the resource utilization and cost reduction of galvanized scum are achieved, which has important economic, social and environmental benefits.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a modified zinc-manganese spinel denitration catalyst based on zinc plating scum. The method comprises the following steps: S1, mixing and stirring the zinc plating scum and a zinc leaching solution, and filtering to obtain a zinc-containing filtrate; s2, sequentially adding the zinc-containing filtrate obtained in the step S1 and a doping agent into an aqueous solution of manganese salt, and uniformly stirring; wherein the dopant is salt containing metal, and the metal is one of nickel, copper, aluminum, tungsten and cobalt; s3, adding a precipitant into the mixed solution obtained in S2, stirring for reaction, after precipitation is completed, evaporating the obtained precipitate and the solution to dryness, and then calcining in an air atmosphere to obtain the modified zinc-manganese spinel denitration catalyst based on the zinc-plating scum. According to the modified zinc-manganese spinel denitration catalyst prepared by the method, the medium and low temperature denitration performance is improved, the preparation cost of the catalyst is effectively reduced, the zinc plating scum which is difficult to treat is eliminated, and the modified zinc-manganese spinel denitration catalyst has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of denitration catalysts, and in particular relates to a preparation method and application of a modified zinc-manganese spinel denitration catalyst based on galvanizing slag. Background Art

[0002] Since the 21st century, environmental governance has been one of the main tasks of protecting the ecology in my country. x ) is one of the main air pollutants and the main cause of greenhouse effect, acid rain, photochemical smog and PM2.5. Selective catalytic reduction (SCR) denitrification technology has a removal rate of more than 90% and is widely used to reduce the emission of nitrogen oxides. At the same time, catalysts with good catalytic performance are the core of SCR technology, so the development of denitrification catalysts is a key link in the popularization of SCR technology.

[0003] Due to the requirements of the production process, the application demand for medium and low temperature denitrification catalysts is relatively large. Manganese-based spinel, as a medium and low temperature denitrification catalyst, has good development prospects. During the catalytic reaction, the manganese-based spinel catalyst can maintain the stability of the structure and prevent the catalyst from obvious aging phenomena such as sintering or hydration. At the same time, the manganese-based spinel structure also provides abundant active sites that can adsorb reactants and promote the reaction. These active sites help to increase the reaction rate and accelerate the reaction kinetics. However, in order to further improve the denitrification efficiency, the catalytic activity of manganese-based spinel needs to be further improved, and the cost of manganese-based spinel needs to be reduced to improve the economy and sustainability of the catalyst. Summary of the invention

[0004] The purpose of the present invention is to provide a preparation method and application of a modified zinc-manganese spinel denitration catalyst based on galvanizing scum. The modified zinc-manganese spinel denitration catalyst prepared by the method improves the medium and low temperature denitration performance, effectively reduces the preparation cost of the catalyst, and absorbs the difficult-to-treat galvanizing scum, and has broad application prospects.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] Provided is a method for preparing a modified zinc-manganese spinel denitration catalyst based on galvanizing slag, comprising the following steps:

[0007] S1, mixing and stirring the galvanizing slag and the zinc leaching solution, and filtering to obtain a zinc-containing filtrate;

[0008] S2, sequentially adding the zinc-containing filtrate obtained in step S1 and a dopant to the aqueous solution of manganese salt, and stirring evenly; wherein the dopant is a salt containing a metal, and the metal is one of nickel, copper, aluminum, tungsten, and cobalt;

[0009] S3. Add a precipitant to the mixed solution obtained in S2, stir to react, evaporate to dryness after precipitation is complete, and then calcine in an air atmosphere to obtain a modified zinc-manganese spinel denitrification catalyst based on galvanizing slag.

[0010] According to the above scheme, in step S1, the zinc leaching solution is a leaching solution with a total ammonia concentration of 5 to 10 mol / L obtained by mixing ammonia water, ammonium bicarbonate and water; preferably, the molar ratio of ammonia water to ammonium bicarbonate is 2 to 10:1.

[0011] According to the above scheme, in step S1, the galvanized slag is a typical metallurgical slag, and its main source is the solid waste generated by ironmaking and steelmaking.

[0012] According to the above scheme, in step S1, the galvanized slag includes elements such as zinc, iron, tungsten, and aluminum, wherein the mass fraction of zinc is more than 92%.

[0013] According to the above scheme, in step S1, the solid-liquid ratio of the galvanizing slag to the zinc leaching solution is 1g:7-13mL.

[0014] According to the above scheme, in step S1, the stirring time is 3 to 6 hours.

[0015] According to the above scheme, in step S2, the doping agent is a nitrate of nickel, copper, aluminum or cobalt, or a tungstate, and the tungstate is preferably ammonium tungstate.

[0016] According to the above scheme, in step S2, the manganese salt is manganese acetate tetrahydrate.

[0017] According to the above scheme, in step S2, the molar ratio of zinc ions to manganese ions is 1:1-3.

[0018] According to the above scheme, in step S2, the molar ratio of the metal element to the zinc ion in the dopant is 0.02-0.1:1.

[0019] According to the above scheme, in step S3, the precipitant is oxalic acid, and the molar ratio of oxalic acid to zinc salt is 2 to 5:1 based on the molar concentration of metal ions and oxalate.

[0020] According to the above scheme, in step S3, the stirring time is 1 to 4 hours.

[0021] According to the above scheme, in step S3, the evaporation process is: evaporation at 100-110° C. for 12-24 hours.

[0022] According to the above scheme, in step S3, the calcination process is: calcination at 500-600° C. for 4-6 hours.

[0023] Provided is an application of a denitration catalyst prepared by the above preparation method in the removal of nitrogen oxides.

[0024] According to the above scheme, the nitrogen oxide is NO.

[0025] According to the above scheme, when the denitration catalyst is used for catalysis, the nitrogen oxide removal rate is 75-92%.

[0026] The present invention provides a method for preparing a modified zinc-manganese spinel denitration catalyst based on galvanized scum, wherein the galvanized scum waste with a high content of zinc is used as the main raw material, and the zinc element in the galvanized scum is extracted by zinc leaching solution to convert all the zinc elements in the galvanized scum into zinc ions and enter the solution, and then manganese ions and a suitable type of dopant are introduced into the solution, and finally the modified zinc-manganese spinel denitration catalyst is obtained by precipitation and calcination; on the one hand, a small amount of other metal element impurities in the zinc extract obtained from the galvanized scum do not have a bad effect on the denitration catalyst, but can be used as a doping modified element to increase the performance of the denitration catalyst, making it possible for the galvanized scum to be used in the preparation of the denitration catalyst. On the other hand, the galvanized scum is introduced into the preparation of the denitration catalyst, which greatly reduces the preparation cost of the catalyst while absorbing the difficult-to-handle galvanized scum, and has important environmental protection and economic benefits. In addition, in combination with a doping metal adapted to the zinc-manganese spinel, the catalytic performance of the zinc-manganese spinel as a denitration catalyst is further improved, and the promotion and application of the zinc-manganese spinel denitration catalyst is promoted.

[0027] Beneficial effects of the present invention:

[0028] 1. The present invention provides a method for preparing a modified zinc-manganese spinel denitrification catalyst based on galvanized slag. The galvanized slag waste is cleverly selected as the zinc source, and then combined with a suitable type of doping metal species to develop a new system of zinc-manganese spinel medium and low temperature (100-220°C) SCR denitrification catalyst. While improving the performance of the denitrification catalyst, it also effectively reduces the preparation cost of the catalyst and consumes the difficult-to-handle galvanized slag, thereby realizing the resource utilization of waste and assisting carbon reduction actions, with significant economic, social and environmental benefits.

[0029] 2. The denitration catalyst preparation process of the present invention is simple and suitable for industrial production.

[0030] 3. The modified zinc-manganese spinel denitration catalyst obtained by the present invention is used for the removal of nitrogen oxides. The appropriate dopant promotes the zinc-manganese spinel Mn 4+ With Mn 3+ The conversion between them forms an electron transfer in the dual redox cycle and adds more acid sites, thereby significantly improving the medium and low temperature denitrification activity of the catalyst. The NO removal rate can be as high as 92%, which has important application prospects. DETAILED DESCRIPTION

[0031] The preparation method of the modified zinc-manganese spinel denitration catalyst based on galvanizing slag of the present invention is described in detail with reference to the examples.

[0032] In the embodiment of the present invention, an Optima 4300DV full spectrum direct reading inductively coupled plasma emission spectrometer is used to detect the main metal ion components in the galvanizing slag. The instrument is produced by Perkin Elmer Company of the United States, and the measurable wavelength range is: 165nm~782nm, and the spectral resolution is: 0.006nm (200nm). The galvanizing slag mainly contains zinc, iron, tungsten, aluminum and other elements, and their mass fractions are 92.46%, 2.03%, 1.27% and 1.07% respectively.

[0033] In the embodiments of the present invention, a D8Advance X-ray diffractometer is used for XRD testing. The instrument is produced by Bruker, Germany, and the instrument parameters are as follows: rated output power is 3kW, Cu target (Kα ray), and tube voltage is 40kV. According to the junction detection, the modified zinc-manganese spinel denitration catalyst prepared in the embodiments has zinc-manganese spinel as the main phase.

[0034] The catalyst denitrification activity was tested using a quartz tube reactor and an FGA10 infrared flue gas analyzer. The test conditions were: total gas flow rate of 1120 sccm, 750 ppm NH3, 3% O2, 700 ppm NO, and N2 as the balance gas. The flow rates of various gas concentrations were controlled by a mass flow meter (calculated by volume fraction). The catalyst denitrification rate was calculated as follows: η = ([NO] 入 -[NO] 出 ) / [NO] 入 ×100%, where [NO] 入 and [NO] 出 They represent the NO concentration at the inlet and outlet, i.e. before and after the reaction, respectively.

[0035] Comparative Example 1

[0036] Add 50 mL of deionized water to a beaker, take 9.8036 g of manganese acetate tetrahydrate and 4.3902 g of zinc acetate dihydrate and dissolve them in deionized water, control the molar ratio of zinc ions to manganese ions to be 1:2, and start stirring. After the solid is completely dissolved, add 7.5642 g of oxalic acid dihydrate to the beaker, and the molar ratio of oxalate to zinc ions is 3:1. Then stir for 3 hours, transfer the sample to an oven at 110 ° C for evaporation and drying for 24 hours. Put the dried mixture into a muffle furnace and calcine at 600 ° C for 4 hours, and finally grind to obtain a zinc-manganese spinel denitrification catalyst.

[0037] The nitrogen oxide removal rate of the zinc-manganese spinel denitration catalyst was tested using Comparative Example 1. It was found through experiments that at 220° C., the NO removal rate reached 67%.

[0038] Comparative Example 2

[0039] 100 g of galvanized slag and 700 g of leaching solution with a total ammonia concentration of 6 mol / L (mixed with ammonia water, ammonium bicarbonate and water, with a molar ratio of ammonia water to ammonium bicarbonate of 3:1) were put into a reactor, stirred at room temperature for 5 h and filtered to obtain a zinc-containing filtrate.

[0040] Take 9.8036g of tetrahydrate manganese acetate and dissolve it in 50ml of deionized water, start stirring and mix evenly. Under stirring, directly add 9.7mL of the above zinc-containing filtrate (wherein the molar number of zinc is 0.02mol) to the above manganese-containing solution, and the molar ratio of zinc ion to manganese ion is controlled to be 1:2. Then, add 7.5642g of dihydrate oxalic acid, and the molar ratio of oxalate to zinc ion is 3:1. Then, stir for 3h, put the sample into an oven at 110℃ for evaporation and drying for 24h, and calcine at 600℃ in a muffle furnace for 4h. After calcination, grind to obtain a zinc-manganese spinel denitrification catalyst.

[0041] Comparative Example 2 was used to test the nitrogen oxide removal rate of the zinc-manganese spinel denitrification catalyst. It was found through experiments that at 220°C, the NO removal rate reached 70%. Compared with the case of using pure zinc salt as the zinc source in Comparative Example 1, the NO removal rate did not decrease, but increased by 3%. This shows that it is feasible to use galvanizing slag as a zinc source, and the catalytic performance can be improved to a certain extent.

[0042] Example 1

[0043] 100 g of galvanized slag and 700 g of leaching solution with a total ammonia concentration of 6 mol / L (mixed with ammonia water, ammonium bicarbonate and water, with a molar ratio of ammonia water to ammonium bicarbonate of 3:1) were put into a reactor, stirred at room temperature for 5 h and filtered to obtain a zinc-containing filtrate.

[0044] Take 9.8036g of tetrahydrate manganese acetate and dissolve it in 50ml of deionized water, start stirring and mix evenly. Under stirring conditions, add 9.7mL of the above zinc-containing filtrate (wherein the molar number of zinc is 0.02mol) and 0.7503g of aluminum nitrate nonahydrate directly to the above manganese-containing solution in sequence, the molar ratio of zinc ion to manganese ion is 1:2, and the molar ratio of aluminum ion to zinc ion is 1:10; mix evenly. Then, add 7.5642g of dihydrate oxalic acid. Then, stir for 3h, put the sample into an oven for evaporation and drying at 110℃ for 24h, and calcine in a muffle furnace at 600℃ for 4h. After calcination, grind to obtain an aluminum-doped zinc-manganese spinel denitrification catalyst.

[0045] The nitrogen oxide removal rate of the aluminum-doped zinc-manganese spinel denitration catalyst was tested using Example 1. It was found through experiments that at 220° C., the NO removal rate reached 92%.

[0046] Example 2

[0047] 100 g of galvanized slag and 700 g of leaching solution with a total ammonia concentration of 6 mol / L (mixed with ammonia water, ammonium bicarbonate and water, with a molar ratio of ammonia water to ammonium bicarbonate of 3:1) were put into a reactor, stirred at room temperature for 5 h and filtered to obtain a zinc-containing filtrate.

[0048] Take 9.8036g of tetrahydrate manganese acetate and dissolve it in 50ml of deionized water, start stirring and mix evenly. Under stirring conditions, add 9.7mL of the above zinc-containing filtrate and 0.4832g of copper nitrate trihydrate directly to the above manganese-containing solution in sequence, the molar ratio of zinc ion to manganese ion is 1:2, and the molar ratio of copper ion to zinc ion is 1:10; mix evenly. Then, add 7.5642g of dihydrate oxalic acid. Then, stir for 3h, put the sample into an oven for evaporation and drying at 110℃ for 24h, and calcine at 600℃ in a muffle furnace for 4h. After calcination, grind to obtain a copper-doped zinc-manganese spinel denitrification catalyst.

[0049] The nitrogen oxide removal rate of the copper-doped zinc-manganese spinel denitration catalyst was tested using Example 2. It was found through experiments that at 220° C., the NO removal rate reached 79%.

[0050] Example 3

[0051] 100 g of galvanized slag and 700 g of leaching solution with a total ammonia concentration of 6 mol / L (mixed with ammonia water, ammonium bicarbonate and water, with a molar ratio of ammonia water to ammonium bicarbonate of 3:1) were put into a reactor, stirred at room temperature for 5 h and filtered to obtain a zinc-containing filtrate.

[0052] Take 9.8036g of manganese acetate tetrahydrate and dissolve it in 50ml of deionized water, start stirring and mix evenly. Under stirring conditions, add 9.7mL of the above zinc-containing filtrate and 0.5816g of nickel nitrate hexahydrate directly to the above manganese-containing solution in sequence, the molar ratio of zinc ion to manganese ion is 1:2, and the molar ratio of nickel ion to zinc ion is 1:10; mix evenly. Then, add 7.5642g of oxalic acid dihydrate. Then, stir for 3h, put the sample into an oven and evaporate and dry it at 110℃ for 24h, and calcine it at 600℃ in a muffle furnace for 4h. After calcination, grind to obtain a nickel-doped zinc-manganese spinel denitrification catalyst.

[0053] The nitrogen oxide removal rate of the nickel-doped zinc-manganese spinel denitration catalyst was tested using Example 3. It was found through experiments that at 220° C., the NO removal rate reached 83%.

[0054] Example 4

[0055] 100 g of galvanized slag and 700 g of leaching solution with a total ammonia concentration of 6 mol / L (mixed with ammonia water, ammonium bicarbonate and water, with a molar ratio of ammonia water to ammonium bicarbonate of 3:1) were put into a reactor, stirred at room temperature for 5 h and filtered to obtain a zinc-containing filtrate.

[0056] Take 9.8036g of tetrahydrate manganese acetate and dissolve it in 50ml of deionized water, start stirring and mix evenly. Under stirring conditions, add 9.7mL of the above zinc-containing filtrate and 0.5300g of ammonium tungstate directly to the above manganese-containing solution in sequence, the molar ratio of zinc ion to manganese ion is 1:2, and the molar ratio of tungsten ion to zinc ion is 1:10; mix evenly. Then, add 7.5642g of dihydrate oxalic acid. Then, stir for 3h, put the sample into an oven and evaporate and dry it at 110℃ for 24h, and calcine it at 600℃ in a muffle furnace for 4h. After calcination, grind to obtain a tungsten-doped zinc-manganese spinel denitrification catalyst.

[0057] The nitrogen oxide removal rate of the tungsten-doped zinc-manganese spinel denitration catalyst was tested using Example 4. It was found through experiments that at 220° C., the NO removal rate reached 75%.

[0058] Example 5

[0059] 100 g of galvanized slag and 700 g of leaching solution with a total ammonia concentration of 6 mol / L (mixed with ammonia water, ammonium bicarbonate and water, with a molar ratio of ammonia water to ammonium bicarbonate of 3:1) were put into a reactor, stirred at room temperature for 5 h and filtered to obtain a zinc-containing filtrate.

[0060] Take 9.8036g of tetrahydrate manganese acetate and dissolve it in 50ml of deionized water, start stirring and mix evenly. Under stirring conditions, add 9.7mL of the above zinc-containing filtrate and 0.58206g of hexahydrate cobalt nitrate directly to the above manganese-containing solution in sequence, the molar ratio of zinc ion to manganese ion is 1:2, and the molar ratio of cobalt ion to zinc ion is 1:10; mix evenly. Then, add 7.5642g of dihydrate oxalic acid. Then, stir for 3h, put the sample into an oven for evaporation and drying at 110℃ for 24h, and calcine at 600℃ in a muffle furnace for 4h. After calcination, grind to obtain a cobalt-doped zinc-manganese spinel denitrification catalyst.

[0061] The nitrogen oxide removal rate of the cobalt-doped zinc-manganese spinel denitration catalyst was tested using Example 5. It was found through experiments that at 220° C., the NO removal rate reached 87%.

[0062] The above is a detailed description of the present invention, but the present invention is not limited thereto, and various changes can be made within the knowledge scope of technicians in the relevant technical field without departing from the present invention.

Claims

1. A method for preparing a modified zinc-manganese spinel denitration catalyst based on galvanizing slag, characterized in that: The following steps are involved: S1, mixing and stirring the galvanizing slag and the zinc leaching solution, and filtering to obtain a zinc-containing filtrate; S2, sequentially adding the zinc-containing filtrate obtained in step S1 and a dopant to the aqueous solution of manganese salt, and stirring evenly; wherein the dopant is a salt containing a metal, and the metal is one of nickel, copper, aluminum, tungsten, and cobalt; S3. Add a precipitant to the mixed solution obtained in S2, stir to react, evaporate the obtained precipitate together with the solution after precipitation is complete, and then calcine in an air atmosphere to obtain a modified zinc-manganese spinel denitrification catalyst based on galvanizing slag.

2. The preparation method according to claim 1, characterized in that: In the step S1, the zinc leaching solution is a zinc leaching solution obtained by mixing ammonia water, ammonium bicarbonate and water and having a total ammonia concentration of 5 to 10 mol / L.

3. The preparation method according to claim 1, characterized in that: The mass fraction of zinc in the galvanizing slag is above 92%.

4. The preparation method according to claim 1, characterized in that: In the step S1, the solid-liquid ratio of the galvanizing slag to the zinc leaching solution is 1 g:7-13 mL.

5. The preparation method according to claim 1, characterized in that: In step S2, the manganese salt is manganese acetate tetrahydrate; the dopant is nitrate of nickel, copper, aluminum or cobalt, or tungstate.

6. The preparation method according to claim 1, characterized in that: In the step S2, the molar ratio of zinc ions to manganese ions is 1:1-3; the molar ratio of metal elements in the dopant to zinc ions is 0.02-0.1:

1.

7. The preparation method according to claim 1, characterized in that: In step S3, the precipitant is oxalic acid, and the molar ratio of oxalic acid to zinc salt is 2 to 5:1 based on the molar concentration of metal ions and oxalate.

8. The preparation method according to claim 1, characterized in that: In the step S1, the stirring time is 3 to 6 hours; in the step S3, the stirring time is 1 to 4 hours.

9. The preparation method according to claim 1, characterized in that: In step S3, the evaporation process is: evaporation at 100-110° C. for 12-24 hours; and the calcination process is: calcination at 500-600° C. for 4-6 hours.

10. Use of a denitration catalyst prepared by the preparation method according to any one of claims 1 to 9 in the removal of nitrogen oxides.